Intracranial vessel wall imaging: current applications and clinical implications. Issue 1 (December 2016) - Kontzialis, Marinos; Wasserman, Bruce
Abstract Conventional CT, MR, and digital subtraction angiography rely on the presence of luminal narrowing for the identification of vascular pathology offering limited insight into the offending pathophysiologic mechanism affecting the vessel. High-resolution MRI vessel wall imaging (VWI) has the potential to directly depict and characterize vessel wall pathology affecting the intracranial circulation increasing diagnostic accuracy for vasculopathies with similar angiographic findings.